ACUTE DIGESTIVE DISORDERS IN INFANTS ON INTRODUCTION OF ADDITIONAL FEEDING - M. Yu. Denisov ("Paediatrician" Publishers LLC, 2012)
This article contains information on digestive disorders developing in infants when introducing the additional food. Physiologic, age-dependent and nutritive preconditions for the development of such disorders, classification of the complications occurring on introducing of the new foodstuffs are represented in the article. The authors also describe clinical presentation and treatment management of the patients with nutritive dietary breach, resulting in digestive disorders and/or allergic reactions.